Evaluación de un protocolo anestésico basado en ketamina y dexmedetomidina en conejos (Oryctolagus cunículus). - Aroca Naula, Oscar Alexander (2025)
The objective of the research was to evaluate an anesthetic protocol of ketamine and dexmedetomidine in rabbits (Oryctolagus cuniculus). Twenty healthy adult animals, between 6 months and 1 year of age, were selected and divided into two groups: a group as protocol of ketamine, midazolam, propofol and sevoflurane (KMPS), and group corresponding to the protocol of ketamine and dexmedetomidine (KD); in which heart rate, respiratory rate, oxygen saturation, rectal temperature, anesthetic effect were evaluated, which was analyzed using the Aldrete post-anesthetic recovery scale, and finally the level of anesthetic depth using the anesthetic states scale and the attributed scale. The results showed that the heart rate showed a significant difference between both groups in all the minutes analyzed, unlike the variables respiratory rate, oxygen saturation, rectal temperature and time or anesthetic effect that did not show a significant difference between them, finally the variable anesthetic depth determined that both anesthetic protocols maintained a type 4 surgical anesthesia in 95% of a total of 20 rabbits analyzed. Therefore, it is concluded that the anesthetic group KD is safe to be used as an anesthesia protocol in rabbits, since the variables studied and compared with the KMPS protocol did not present risks that compromised the life of the anesthetized rabbits in the present investigation.